Biostimulant activity of Galaxaura rugosa seaweed extracts against water deficit stress in tomato seedlings involves activation of ABA signaling - Morales-Sierra, Sarai; Luis, Juan Cristo; Jiménez-Arias, David; Rancel-Rodríguez, Nereida M.; Coego, Alberto; Rodriguez, Pedro L.; Cueto, Mercedes; Borges, Andrés A. (Frontiers in Plant Science, 2023)
Water scarcity is a serious constraint for agriculture, and global warming and climate change can exacerbate it in many areas. It is therefore necessary to implement sustainable approaches to deal with current and future water scarcity scenarios. Both genetic and chemical approaches are being applied to manage this limitation and maintain crop yields. In particular, biostimulants obtained from natural sources are promising aids for coping with water deficit stress in agriculture. In particular, marine algae are a rich source of such bioactive compounds, among many others. As a result, their study has become increasingly important in recent years. The research is focused on discovering new sources of biostimulants and understanding their mechanism of action. Coastal oceanic islands are a tremendous source of biodiversity, offering greater biological and chemical diversity than terrestrial systems. This makes them a rich resource for bioprospecting for molecules with biotechnological applications. Here we present a bioprospection study of nine macroalgal (seaweed) extracts from the north coast of Tenerife, in the Canary Islands. Four aqueous extracts from these macroalgae show biostimulant activity against water deficit stress in tomato seedlings under controlled conditions, providing higher tolerance than the mock-treated control. Among them, the Galaxaura rugosa extract showed the highest biostimulant activity against water deficit stress. We demonstrate that this positive effect involves activation of the ABA pathway in both Arabidopsis thaliana and tomato. Application of G. rugosa extract to the root system by drenching tomato seedlings subjected to water deficit leads to improvement in CO2 assimilation and water use efficiency (WUEp), compared to mock-treated plants. In summary, these results highlight a new potential seaweed source of substances with osmoprotectant properties, useful for biostimulant development. Future studies may provide further insight into which components of the seaweed extract induce activation of the ABA pathway.